Catalytic activity of TiO2/sepiolites in the degradation of Rhodamine B aqueous solution - Thao, Nguyen Tien; Huong Ly, Doan Thi; Hoan, Doan Minh; Phuong Nga, Han Thi (Vietnam Journal of Chemistry, 2017)
TiO2/sepiolite catalysts were prepared by suspension of titanium dioxide and support in solvent accompanying by calcination. The characterization of the obtained powder has been examined by some physical means including XRD, SEM, FT-IR, and UV-vis. The sepiolite support possesses fibrous structure. X-ray diffraction analysis pointed out that the TiO2 particles are firmly distributed on fibrous sepiolite matrix. All TiO2/sepiolite samples were tested for the degradation of rhodamine B and showed a high catalytic activity. The experimental data showed that the degradation efficiency of rhodamine B is correlated with the amount of TiO2 loadings and oxidant behavior. At room temperature, the conversion of rhodamine B reaches to 99-100 % over 6.0 wt% TiO2/sepiolite catalyst. Keywords. TiO2, rhodamine B, sepiolite, degradation, photocatalysis.